Exploring the interrelationships among operations management practices, customer perceptions of service quality and performance of hotels - Al-Zaidi, Asma Nasser Mohammed (2012)
Hospitality and tourism are important sectors of any economy. In the service sector, achieving a level of service quality that satisfies customers usually results in a competitive advantage in the market. The concept of service quality in hotels has been the subject of many research studies and there are numerous published works in the field. However, only a few studies have focused on the determinants of service quality for hotels using a set of comprehensive criteria. Thus, conceptualizing a service quality model that identifies the dimensions of service quality that affect customers' satisfaction is needed for hotels. In addition, the role of operations management practices in managing service quality cannot be denied. The available literature on the hotel industry in terms of managerial practices is unfortunately poor and needs to be enriched. Logically, better operations management practices in managing hotels' service quality would have a direct positive impact on performance, but there could also be some indirect (mediating) impact on performance through customer satisfaction.